Pengaruh Kualitas Produk dan Inovasi Terhadap Keunggulan Bersaing UMKM Kuliner di Masa Pandemi Covid-19 - Dahmiri Dahmiri; Sylvia Kartika Wulan Bhayangkari; Idham Khalik (Universitas Batanghari Jambi, 2021)
This study aims to analyze the effect of product quality and innovation variables on the competitive advantage of Culinary MSMEs during the Covid-19 pandemic. In this study, the population was 100 culinary SMEs in Jambi City. Primary data was obtained by giving a statement in the form of a questionnaire, while the technique used was simple random sampling. To analyze the data, descriptive and quantitative methods were used and the analytical tool used was multiple linear regression. The results of the study concluded that the product quality and innovation variables had a positive and significant effect on the competitive advantage variable partially. The results of the simultaneous testing of product quality and innovation variables showed that it had a positive and significant effect on the competitive advantage of Culinary MSMEs during the COVID-19 pandemic in Jambi City.